2019
DOI: 10.1038/s41598-019-44394-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Thermal-sensitive Multi-transform Actuator

Abstract: Controllable and miniaturised mechanical actuation is one of the main challenges facing various emerging technologies, such as soft robotics, drug delivery systems, and microfluidics. Here we introduce a simple method for constructing actuating devices with programmable complex motions. Thermally responsive hydrogels based on poly( N -isopropylacrylamide) (PNIPAM) and its functionalized derivatives (f-PNIPAM) were used to control the lower critical solution temperature (LCST) or the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Overall, the greater C-dot concentration was responsible for modulation of the swelling property and LCST of PNIAPM . Previous studies reported a similar effect of PNIPAM phase transitions upon incorporation of guest species within the polymer matrix. , …”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Overall, the greater C-dot concentration was responsible for modulation of the swelling property and LCST of PNIAPM . Previous studies reported a similar effect of PNIPAM phase transitions upon incorporation of guest species within the polymer matrix. , …”
Section: Resultsmentioning
confidence: 53%
“…44 Previous studies reported a similar effect of PNIPAM phase transitions upon incorporation of guest species within the polymer matrix. 45,46 3. mg/mL) in comparison with a bare CMC−PNIPAM gel not containing C-dots. Indeed, the data in Figure 4 demonstrate that inclusion of the C-dots in the CMC−PNIPAM hydrogel yielded a superior desalination performance.…”
Section: Resultsmentioning
confidence: 99%
“…Its structure is well defined, and its tunable LCST is close to human body temperature. [34,35] Figure 4B shows a thermoresponsive hydrogel with a gradient pore structure expanding and contracting in response to changes in temperature. [84] The usage of hydrogel is highly preferable in applications where biocompatibility is essential.…”
Section: Hydrogelsmentioning
confidence: 99%
“…Using this technique, they fabricated a bioinspired artificial flower with two distinct LCSTs (48° and 60.8°) (Figure 11E,F). [35] Figure 11. Thermoresponsive actuators.…”
Section: Materials Solubility Changementioning
confidence: 99%
See 1 more Smart Citation